Flow Garden - (:unkn) unknown (My University, 2022)
Το έργο αποτελεί μια σύμπραξη με την εικαστιό Σωτηρία-Αρσινόη Τσορμπάρη. Δημιουργήσαμε μια έκθεση η οποία πραγματοποιήθηκε στη Φλώρινα. Σκοπός μας ήταν να φτιάξουμε ένα διακαλλιτεχνικό έργο και να δημιουργήσουμε μια κοινή γλώσσα μεταξυ του ηχοτοπίου και της τοπιογραφίας.

The project is a collaboration with the artist Sotiria-Arsinoi Tsorparis. We created an exhibition which took place in Florina. Our purpose was to make an interdisciplinary project and to create a common language between the art of soundscape and landscape .
Flow Garden
Keywords: Ηχοτοπίο, Tοπιογραφία, Ζωγραφική, Ηχητική εγκατάσταση; Soundscape. Landscape, Painting, Sound Installation